Rapid Access to Azabicyclo[3.3.1]nonanes by a Tandem Diverted Tsuji–Trost Process - Steeds, Hannah G. (Chemistry, 2020)
A three‐step synthesis of the 2‐azabicyclo[3.3.1]nonane ring system from simple pyrroles, employing a combined photochemical/palladium‐catalysed approach is reported. Substrate scope is broad, allowing the incorporation of a wide range of functionality relevant to medicinal chemistry. Mechanistic studies demonstrate that the process occurs by acid‐assisted C−N bond cleavage followed by β‐hydride elimination to form a reactive diene, demonstrating that efficient control of what might be considered off‐cycle reactions can result in productive tandem catalytic processes. This represents a short and versatile route to the biologically important morphan scaffold.